Implementation of Simak Takrir Bil Ghoib: (Case Study at Tahfizhul Qur'an Putri Islamic Boarding School Al-Lathifiyyah Palembang) - Rita Yulia Anggraini; Ida Bagus Benny Surya Adi Pramana; Lusi Endang Sri Darmawati; Wulan Indah Fatimatul Djamilah; Afif Alfiyanto; Durotut Takiyah; Fitri Hidayati (EDUKASI : Jurnal Pendidikan Islam (e-Journal), 2022)
The purpose of this study was to determine the process of implementing the takrir bil-ghoib program and the inhibiting and supporting factors. The type of research used is a qualitative field research type. This research was conducted at the Pondok Pesantren Tahfizhul Qur'an Putri Al-Lathifiyyah Palembang. Data collection techniques used are observation, interviews, and documentation. Data reduction, data presentation, and conclusion drawing are the analytical techniques used. The research results are 1) the implementation of the takrir bil-ghoib program has been implemented optimally even though it has not yet received maximum results. Islamic boarding schools have done their best to support the program's success, but many students still have not implemented the program properly and still need a lot of encouragement and strict supervision; 2) the supporting factor is an intense desire and support from all parties. The inhibiting factor is the lack of sincerity from some students. It requires strong motivation. The researcher concludes that implementing the takrir bil-ghoib program will get maximum results if all students cooperate in supporting this program.